Epidemiological profile of fetal malformations of regions 29 and 30 of the 16th Regional Health Coordination of the State of Rio Grande do Sul (Research, Society and Development, 2020)
The gestation period is marked by major changes. It is an intense experience, with contrasting feelings and doubts. In order to improve the quality of care in prenatal care, childbirth and the newborn, the Ministry of Health established the Rede Cegonha. However, some unexpected events can occur, such as fetal death. The objective of this study was to outline a profile of the sociodemographic factors of mothers whose pregnancies evolved to fetal deaths due to congenital malformations, to characterize the conditions of pregnancies and to analyze pregnancies that evolved to fetal deaths due to congenital malformations. This is a cross-sectional, exploratory, descriptive study with a qualitative and quantitative approach, using information from the Fetal and Infant Mortality Committee Investigation Forms, analyzing the period from 2014 to 2018. The main results were that most of the mothers are over 35 years old, white, have elementary education, live with the child's father or partner, have paid work, live in an urban area, do not use tobacco, alcohol or other drugs, have used any type of medication during pregnancy and did not have any chronic or other diseases. Regarding pregnancy variables, it was observed that most fetal deaths from malformation occurred in the first pregnancy of these women, had no previous abortions, the pregnancy that evolved to fetal death from malformation was a planned pregnancy, started prenatal care at seven weeks , had seven prenatal consultations, did not present any disease acquired during the investigated pregnancy and chose the public sector to carry out prenatal care. As for the fetus, it was observed that the majority were male, being classified as non-preventable deaths, only four cases as preventable and the type of congenital malformation, cardiac was the most evident in the cases analyzed. With the results, it is expected to make visible the current situation of fetal mortality in the region and from there to outline strategies for the prevention and avoidability of these deaths, thus reducing their rates.